Prevention of macular edema and secondary degeneration of the macula and posterior pole in anterior uveitis - N.V. Konovalova; N.I.Khramenko; O.V. Guzun (Ukrainian Society of Ophthalmologists, 2019)
Background. Endogenous uveitis is an inflammatory disease of the uvea, making up to 30% in the ophthalmology overall structure according to various authors. Uveitis is among current socially important issues in ophthalmology due to significant incidence rates mainly in people of young and working age; visual impairment and blindness occur in 17.7%-19.2-35% of patients. Purpose. To improve the treatment efficacy in patients with anterior uveitis using Indocollyre® electrophoresis and Indocollyre® instillations in order to prevent macular edema and secondary degeneration of the macular and the anterior pole. Material and Methods. Fifty-four patients (54 eyes) with anterior uveitis were followed up. All patients were performed biomicroscopy, ophthalmoscopy, intraocular pressure measurements, perimetry, and ophthalmic rheography using a parameter of pulse volume, the Rheographic Quotient (RQ) (‰) (ReoCom, Ukraine). Optical coherent tomography (OCT) visualized structural changes not only in the sensory retina but in the choroid, which makes it possible to assess the inflammation process in the eye and to early diagnose and to prevent potential complications. Fluorescein angiography (FAG) was performed in order to assess the pigment epithelium, sensory epithelium, and vessels as well as to reveal drusen and the accumulation of lipofuscin in the retina. Results. OCT findings give the evidence of the presence of macular edema if the retina thickness is increased in the fovea (>240 µm). This is evidenced by the FAG findings and revealed difference in the rheographic quotient value of more than 64% in 21 patients, which made it possible to predict the risk of a dry form of macular dystrophy in these patients. Timely prescription of Indocollyre® electrophoresis and instillations advanced macular edema resolution, which contributed to significant improvement of visual acuity in the iridocyclitis patients, as much as twice, in both groups. The mean treatment course in an acute process was 10±1.8 days. Conclusion. It is reasonable to use Indocollyre® electrophoresis and instillations to prevent such anterior uveitis complications as macular edema and secondary macular degeneration.